Debate on the Application of Discourse Analysis in Geo-Environment Studies - Yuan Guangsheng (Editorial Committee of Tropical Geography, 2021)
Although political geography has been gaining popularity in China as a sub-discipline of human geography, its methodological development has been limited to the quantitative paradigm. As a widely used research method in social sciences, discourse analysis remains under-used in Chinese geo-environment analyses. This study discusses the application status and prospects of discourse analysis methods in geo-environment analysis within the Chinese scholarship. First, this study discriminates the concepts, theories, and analysis paths involved in discourse analysis methodology. Specifically, it discusses how discourse is conceptualized compared to text, language, discourse formation, discourse structure, textual analysis, and content analysis. Subsequently, the study discusses various case studies of discourse analysis in human geography, which focuses on the application of the discourse analysis method in geo-environment analyses. Additionally, the study introduces other commonly used research methods in geo-environment analyses, to deepen readers' awareness of the characteristics of discourse analysis. Further, it discusses other possibilities of discourse analysis in future geo-environment analyses. By doing so, this study highlights the status and importance of discourse analysis within Chinese political geography. On this basis, this study uses an empirical case study from the Journal of Contemporary China to discuss global perceptions of China's rise, thus providing an accurate practical guide to explain how discourse analysis should be expanded in empirical case studies. Then, this study addresses the challenges and potential of discourse analysis in the background of an emerging Big Data era. Finally, the study combines the current background of continuous innovation in geographical research methods with discourse analysis. Accordingly, it discusses the possible future role of discourse analysis as a relatively traditional research method in geopolitics, or more generally, within human geography.